Resting and postexercise heart rate variability in professional handball players - Kayacan, Y.; Yildiz, S. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The aim of this study was to evaluate heart rate variability (HRV) in professional handball players during rest and following a 5 min mild jogging exercise. METHODS: For that purpose, electrocardiogram (ECG) of male handball players (N.=12, mean age 25±3.95 years) and sedentary controls (N.=14, mean age 23.5±2.95 years) were recorded for 5 min at rest and just after 5 min of mild jogging. ECGs were recorded and following HRV parameters were calculated: time-domain variables such as heart rate (HR), average normal-to-normal RR intervals, standard deviation of normal-to-normal RR intervals, square root of the mean of the squares of differences between adjacent NN intervals, percentage of differences between adjacent NN intervals that are greater than 50 milliseconds (pNN50), and frequency-domain variables such as very low frequency, low (LF) and high frequency (HF) of the power and LF/HF ratio. Unpaired/-test was used to find out differences among groups while paired/-test was used for comparison of each group for pre- and postjogging HRV. Pearson correlations were carried out to find out the relationships between the parameters. RESULTS: Blood pressures were not different between handball players and sedentary controls but exercise increased systolic blood pressure (P<0.01). HR was increased with exercise (P<0.001) and was slower in handball players (P<0.01). QTc was increased with exercise (P<0.001) and was higher in handball players (P<0.001). Exercise decreased pNN50 values in both groups but LF/HF ratio increased only in sedentary subjects. CONCLUSIONS: In conclusion, results of the HRV parameters show that sympathovagal balance does not appear to change in handball players in response to a mild, short-time (5 min) jogging exercise. However, in sedentary subjects, either the sympathetic regulation of the autonomous nervous system increased or vagal withdrawal occurred.